Tourists’ Perceptions toward Sustainable Tourism at Kuakata, Bangladesh - Sarker, Jashim Uddin; Nahar, Kamrun; Asraf, Md. Aminul (Journal of Tourism & Adventure, 2023)
Sustainable tourism and related externalities are examined from the perspective of travelers in this research. The research involved primary data collection in Kuakata during COVID-19 in March 2021. Correspondence analysis on tourists’ perceptions shows that tourists have an overall concern towards sustainable tourism with respect to the quality of the destination and desirable features. However, they moderately feel that the lack of certain things (i.e. medical and first-aid services, parking areas) is making tourism activities worse and that’s why tourists were unsatisfied. Tourists are also interested in sustainable tourism development. For instance, they prefer to stay in those hotels that are doing well for the environment and also spend extra money on garbage cleaning and village development. Besides, there is a significant mean difference in the perceptions of tourists towards sustainable tourism development at Kuakata sea beach with respect to tourists’ house location from Kuakata sea beach and monthly family income. Furthermore, perceptions and attitudes toward sustainable tourism vary significantly dependent on the characteristics of the visitors.